Anemia and Iron and Vitamin B12 Deficiencies in Children Under 5 in Mexico: Results from the National Health and Nutrition Survey (ENSANUT) - Leal, Cristina Güitrón (Curr Dev Nutr, 2020)
OBJECTIVES: To examine the burden of anemia, iron deficiency, and vitamin B(12) deficiency in children under 5 in Mexico. METHODS: Data from the recently completed National Health and Nutrition Survey (ENSANUT 2018) were analyzed to examine the burden of anemia and micronutrient deficiencies in children under 5 (1 to <5 years). Hemoglobin (Hb) concentrations werequantified in capillary blood samples (n = 3144) via HemoCue.Venous blood samples (n = 1019) were collected, centrifuged, processed, and stored <−80°C until analysis of micronutrient biomarkers. Serum ferritin (SF), C-reactive protein (CRP), and vitamin B(12) concentrations were measured via immunoassays. Hemoglobin was adjusted for altitude; anemia was defined as hemoglobin <11.0 g/dL. Iron deficiency was defined as serum ferritin <12.0 µg/L and iron insufficiency was defined as serum ferritin <20.0 µg/L; inflammation was defined as CRP concentrations > 5.0 mg/L (and CRP > 1.0 mg/L). Iron deficiency anemia was defined as hemoglobin <11.0 g/dL and serum ferritin <12.0 μg/L. Vitamin B(12) deficiency and vitamin B(12) insufficiency were defined as <148.0 and <221.0 pmol/L, respectively. Survey frequency procedures were used to examine the prevalence of anemia and micronutrient deficiencies; survey linear and logistic regression were used to examine associations of micronutrient biomarkers with hemoglobin concentrations and odds of anemia. RESULTS: A total of 22.9% of children were anemic in this population. In the biomarker sub-sample, 10.0% of children were iron deficient (SF < 12.0 µg/L), and 29.9% had serum ferritin concentrations <20.0 µg/L. A total of 9.5% of children had CRP concentrations >5.0 mg/L, and 34.7% had CRP > 1.0 mg/L. The prevalence of vitamin B(12) deficiency (vitamin B(12) < 148.0 pmol/L) was 5.4% and 21.5% of children had vitamin B(12) insufficiency (vitamin B(12) < 221.0 pmol/L). CONCLUSIONS: Findings suggest that the burden of anemia and iron and vitamin B(12) insufficiency is high in young children in Mexico. FUNDING SOURCES: ENSANUT was funded by The Ministry of Health of Mexico.